2017
DOI: 10.1017/s2040470017000802
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral band selection for imaging sensor design for vineyard disease detection: case of Flavescence Dorée

Abstract: Disease detection and control is thus one of the main objectives of vineyard research in France. Monitoring diseases manually is fastidious and time consuming, so current research aims to develop an automatic detection of vineyard diseases. This project explored the use of a high-resolution multi-spectral camera embedded on a UAV (Unmanned Aerial Vehicle) to identify the infected zones in a field. In-field spectrometry studies were performed to identify the best spectral bands for the sensor design. The best m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In one study looking at Huanglongbing (HLB) detection in citrus crops by Garcia-Ruiz and colleagues, it was found that the NIR-R index value and the average reflectance values at spectral bands of 560 nm and 710 nm were statistically different between healthy and HLB-infected trees [29]. Likewise, Flavescence dorée disease in vineyards was detected using a multi-spectral camera monitoring bands at approximately 530-600-650-690-730-750-800 nm, with an accuracy over 94% by Al-Saddik and colleagues [30]. In other studies, vegetation indices were more heavily used.…”
Section: Plant Stress Detectionmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study looking at Huanglongbing (HLB) detection in citrus crops by Garcia-Ruiz and colleagues, it was found that the NIR-R index value and the average reflectance values at spectral bands of 560 nm and 710 nm were statistically different between healthy and HLB-infected trees [29]. Likewise, Flavescence dorée disease in vineyards was detected using a multi-spectral camera monitoring bands at approximately 530-600-650-690-730-750-800 nm, with an accuracy over 94% by Al-Saddik and colleagues [30]. In other studies, vegetation indices were more heavily used.…”
Section: Plant Stress Detectionmentioning
confidence: 97%
“…The majority of UAS-assisted aerial imaging for detection or estimation purposes uses multispectral imaging heavily to calculate vegetation indices such as NDVI and other variants involving NIR data [6,26,33,34,41,68]. A notable exception comes from an article by Al-Saddik and her colleagues which directly used multispectral data programmed to specific bands to detect Flavescence dorée disease in vineyards without using common indices [30].…”
Section: Multispectral and Nir Camerasmentioning
confidence: 99%
“…An RGB-Depth (RGB-D) camera, employed with two grayscale cameras (mvBlueFOX-MLC202bG), covering light sources with polarizing films and the multispectral sensors mounted to UAV platform, was used to monitor orange orchards for detecting citrus greening disease in Florida [50]. Al-Saddik et al [78] used multispectral sensors to differentiate Flavescence dorée diseased and healthy grapevines in a vineyard without using common vegetative indices. Several other studies also used multispectral cameras [36,48,70,[79][80][81][82][83].…”
Section: Multispectral Camerasmentioning
confidence: 99%
“…Precision viticulture is an area of research that includes many applications, such as estimating growth [6], estimating evaporate-transpiration and harvest coefficients [7], vigor evaluation [8], water stress localization [9] or diseases detection [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…So far, there is some researches on the different imaging systems for the VDD. Certain studies use images taken at the vine leaf level [10][11][12][13][14] which can be mounted in mobile robots. Other research is carried out on aerial images taken by drones at plot scale targeting the vine canopies [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%